Diagnosis of Local Isolates of Yeast Saccharomyces cerevisiae by Biochemical Methods - Haitham Aljader; Zena Al_gader (College of Education for Pure Sciences, 2021)
Abstract In this study 10 local isolates of yeast Saccharomyces were obtained from the local markets of Mosul .The Isolates were diagnosed by morphological and cultural characters in addition to biochemical tests. the results of the tests showed that they belong to the Saccharomyces cerevisiae type . Local isolates were tested for resistance to 8 different types of antibiotics and 5 salts of heavy metals. all isolates were resistant to each of Chloramphenicol , Ampicillin , Tetracycline and Streptomycin at 100%. As for the Erythromycin antibiotic most of the local isolates were resistant except for the isolates (SY4 , SY5 , SY6) As well as Amoxicillin all isolates were resistant except for (SY4) . While the isolates showed sensitivity to Nystatin at 80% and for Flagyl at 90% . The isolates also showed resistance to all Zinc chloride ZnCl2 , Nickel chloride NiCl2 and Cobalt chloride CoCl2 at 100% , as for mercury chloride all isolates were resistant except for (SY2) which showed sensitivity to it . sensitivity of the isolates was clear to Cadmium chloride CdCl2 except for the isolates (SY3 , SY9 , SY10) .